Effects of mindfulness and fatigue on emotional processing: an event-related potentials study - Fan, Jialin; Li, Wenjing; Lin, Mingping; Li, Xinqi; Deng, Xinmei (Frontiers in Behavioral Neuroscience, 2023)
Fatigue is a common experience in everyday life. People who experience fatigue will have more intense negative emotions, and at the same time, their positive emotions will decrease, impairing the individual's emotional processing ability. In previous research, mindfulness meditation reduces the intensity of negative emotional stimuli. However, if individuals continue to be affected by negative emotions when they are fatigued, it is unclear whether mindfulness can buffer the effects of fatigue on emotions. This study examined whether mindfulness meditation affects the association between fatigue and emotions, using event-related potentials (ERPs). One hundred and forty-five participants completed the experiment. They were randomly assigned to the Mindfulness or Non-mindfulness group; and they were presented with positive, neutral, or negative pictures in an emotional processing task before and after mindfulness or rest. Late positive potential (LPP) is an important indicator of emotional stimuli perceived by individuals, and positive or negative pictures can induce an increase in LPP amplitude more than neutral pictures. Our findings suggest that fatigue significantly affected individuals' LPP amplitudes in the early, mid, and late windows in the Non-mindfulness group, specifically, the more fatigued individuals had lower LPP amplitudes, but not in the Mindfulness group. These results suggest that in a state of fatigue, mindful individuals are able to maintain responsiveness to emotional stimuli by maintaining LPP amplitude. Our study has demonstrated that mindfulness meditation, to some extent, offsets the negative effect of fatigue on the neural activation of emotion.